Community Structure and Diversity of a Moist Deciduous Forest in Uttar Pradesh - Upadhyay, Ruchi; Singh, Jaswant; Singh, Bajrang (Indian Forester, 2008)
The present study was undertaken in a moist deciduous forest of Indo-Gangetic plain to assess the species structure, population abundance and distribution pattern, regeneration status, diversity and dominance. Three sites selected on the basis of the disturbance gradient showed sequential differences in analytic characters. Population density decreased from 82 ha-1 from site I to 486 ha-1 in site III, where as basal area enhanced from 6.8 m2 ha-1 to 62.2 m2 ha-1 correspondingly. Diversity index and species richness were highest for inner undisturbed site III. Distribution pattern of various growth forms showed mostly the contagious distribution. Population structure of common trees showed poor regeneration and a nonlinear reduction in girth distribution pattern with increasing diameter classes. Mostly forage grasses were found in open forest (site I) whereas ground flora mainly consisted of medicinal herbs in the undisturbed dense forest (site III).